Analisis pembelajaran matematika pada materi peluang dengan pendekatan TPACK dalam perspektif teori belajar konstruktivisme - Nurlita, Maya; Jupri, Al; Priatna, Bambang Avip (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2025)
This study aims to analyze the implementation of mathematics learning on chance materials using the technological pedagogical content knowledge (TPACK) approach from the perspective of constructivist learning theory. Students often experience difficulties in understanding the concept of opportunities due to its abstract nature and lack of contextual visualization, so a learning approach is needed that can bridge the gap between mathematical theory and meaningful learning experiences in the digital era. Data was obtained through a qualitative study using direct observation of the learning process using an observation sheet. The participants were 27 students of class XII and one teacher. The results of the analysis showed that the percentage of learning process achievement was 66.67%. This shows that the TPACK approach has been applied, but not yet optimally in several important aspects. Teachers have applied the TPACK approach, but technology integration has not been maximized.  Reflection and feedback on the learning process have not been implemented thoroughly.